Syllable Structure And Loanword Adaptation In Fròʔò - TRAORE, YRANAHAN; Féry, Caroline (My University, 2019)
This article examines the syllable structure in Fòʔò, a dialect of Tagbana spoken in Côte d'Ivoire. The underlying syllable structure is limited to C(C)V and V syllable, thus syllables with an onset and syllables consisting with a nucleus and nothing else. The onset can be complex, although it is limited to two positions which are restricted in their order by the sonority sequence principle. By contrast, the surface syllables are the result of phonological changes that take place in specific morphological environments. Vowel deletion happens regularly when two identical vowels are separated by a consonant in the context C1V1.C2V2. there is also a process of liquid deletion that simplifies underlying complex onsets. However, when the complex onset is the result of vowel deletion, liquid deletion does not apply: The two processes—syllable become more complex or syllable are simplified—are in a counterfeeding relation to each other. The last process that is described is fusion of two monosyllabic morphemes into a single syllable. If the second morpheme is wí with a glide in its onset, the fusion results in a CV syllable with a round vowel. Otherwise the emerging syllable is CVC where the first CV is the entire first morpheme and the second C is the consonant of the second morpheme. The results of the study of syllable structure is tested on loanwords, where syllables' repairs take place. For instance, codas are avoided by epenthesis and unallowed initial vowels trigger epenthesis of an onset segment [h]. It is also shown how the constraints on syllable structure repair loanwords in Fròʔò
Keywords: Syllable structure; Fròʔò; dialect